Development of guided inquiry learning tools combined with advance organizer to increase students' understanding of physics concept. (April 2020) - Kusdiastuti, M; Gunawan, G; Harjono, A; Nisyah, M; Herayanti, L
Abstract: The combination of guided inquiry learning models combined with advanced organizers is needed to facilitate students who have diverse initial abilities so that they can participate in inquiry activities well. The purpose of this study is to produce a physics learning device in a guided inquiry model that is combined with an advance organizer, who has valid, practical, and effective criteria in improving students understanding of the physics concept. The learning tools testing phase was carried out in class X in one of the high schools in the Mataram, using one group pre-test post-test design. Observation and concept understanding tests do data collection. The results of the study show that: Learning tools developed are valid; The practicality of learning tools was tested through the implementation of physics learning by the guided inquiry model combined with advance organizer, and the effectiveness of the learning tools can increase student understanding of physics concepts. These results indicate that the learning device developed has valid, practical, and effective criteria to increase student' understanding of the physics concept.